Giant fibrovascular polyps of the esophagus. Trans oral versus surgical approach. Case report and systematic literature review. (August 2022) - Ferri, Valentina; Vicente, Emilio; Quijano, Yolanda; Duran, Hipolito; Diaz, Eduardo; Fabra, Isabel; Malave, Luis; Ruiz, Pablo; Isernia, Roberta; Caruso, Riccardo
Abstract: Introduction: Giant fibrovascular esophageal polyp is a rare benign intraluminal tumour. The aim of this study is to perform a review of the most recent literature in order to describe and analyse the current range of possible diagnostics and treatment strategies. Case report: We present two cases of giant fibrovascular esophageal polyp treated with a combined minimally invasive transluminal approach at Sanchinarro University Hospital. Further, we perform a literature review. Conclusion: We present two cases of grant fibrovascular polyp submitted to minimally invasive transluminal approach. Furthermore, 54 original articles reporting 59 cases have been analysed. In the surgical group, an esophagotomy and polyp resection were performed in 31 (91 %) patients and a total esophagectomy in two patients (5, 8 %). Severe morbidity occurred in two patients (5, 8 %.) The median hospital stay was 9.25 days. A total of two (5, 8 %) cases of recurrence have been registered. In the minimally invasive transluminal approach group, 27 patients had a polyp resection performed completely by endoscopy/transoral. There were no complications but there was one case of recurrence. Conclusion: The transluminal approach is safe and should be considered also in the treatment of large esophageal polyps. Highlights: Giant fibrovascular polyps (GFE) of the esophagus are rare, benign tumors arising from the cervical esophagus or hypopharynx. GFE exeresis is mandatory and can be carry on by conventional surgery (cervicotomy or thoracothomy) or by minimally invasive transluminal approach The minimally invasive transluminal approach is feasible and present advantages with respect to the conventional surgical approach